Analisis Miskonsepsi Materi Fluida Statis Menggunakan Four Tier Diagnostic Test pada Siswa SMA - Nenden Farida Alia; Irma Fitria Amalia; Rizal Adimayuda (Jurnal Pendidikan dan Ilmu Fisika, 2026)
This study aims to analyze students' misconceptions on the static fluid concept using a Four-Tier Diagnostic Test instrument. Static fluid material was chosen because of its complex characteristics and potential to cause misconceptions, particularly in the sub-concepts of hydrostatic pressure, Pascal's law, and Archimedes' principle. This study used a descriptive method with a quantitative approach. The subjects were 68 eleventh-grade students from a public senior high school in Garut Regency, selected through purposive sampling. The research instrument consisted of a four-tier diagnostic test comprising 15 multiple-choice items. The data obtained were analyzed based on the combination of students' answers at each tier to identify categories of conceptual understanding, misconception, lack of understanding, and partial understanding. The results showed that overall, 37.74% of students experienced misconceptions, 37.65% understood the concept, 14.31% did not understand the concept, and 10.30% partially understood the concept. At the sub-concept level, the highest misconception was found in Pascal's law (52.20%), followed by Archimedes' principle (41.47%) and hydrostatic pressure (25%). The highest item-level misconception occurred in item number 7 concerning the lifting force on a piston, with a percentage of 73.53%. These results indicate the need for more serious efforts in identifying and remediating student misconceptions, as well as the importance of applying in-depth diagnostic instruments such as the Four-Tier Diagnostic Test in physics learning.